KEYAKINAN MATEMATIS DAN KEMANDIRIAN BELAJAR MAHASISWA PADA PROGRAM STUDI PENDIDIKAN MATEMATIKA [MATHEMATICAL BELIEFS AND THE SELF-REGULATED LEARNING OF STUDENTS IN A MATHEMATICS EDUCATION STUDY PROGRAM] - Soesanto, Robert Harry; Rahayu, Wardani; Kartono, Kartono (Universitas Pelita Harapan, 2020)
In general, integral calculus courses are difficult for students because the problems involved require strong problem-solving skills. For university students, integral calculus courses also require them to do self-regulated, or independent, learning. Another aspect that makes learning difficult for these students is their mathematical beliefs and prior knowledge. This study aims to see how different types of mathematical beliefs affect self-regulated learning in terms of students' prior knowledge. This research was conducted on students in a mathematics education study program at a private university in Tangerang with a sample of 120 students. This research is an ex post facto quantitative study using a two factorial design. The variables in this study consisted of independent variables in the form of mathematical beliefs, the moderator variable in the form of students’ prior knowledge, and the dependent variable in the form of self-regulated learning. The results obtained are: (1) self-regulated learning by students with logical consistency mathematical beliefs is higher than students with memorized and procedural beliefs, (2) there is an interaction between mathematical beliefs and prior knowledge towards self-regulated learning, (3) student in the high prior knowledge gorup logical consistency beliefs had higher self-regulated learning than students with memorized and procedural beliefs, and (4) self-regulated learning in the low mathematics prior knowledge group with logical consistency beliefs is lower than students with memorized and procedural beliefs.BAHASA INDONESIA ABSTRACT: Mata kuliah kalkulus integral pada umumnya masih menjadi kesulitan bagi mahasiswa karena permasalahan yang terkandung membutuhkan pemecahan masalah yang kuat. Kalkulus integral juga membutuhkan kemandirian belajar bagi mahasiswa yang mempelajarinya. Hal lain yang menjadi kesulitan mahasiswa adalah faktor keyakinan matematis dan pengetahuan awal matematis. Penelitian ini bertujuan untuk melihat perbedaan jenis keyakinan matematis terhadap kemandirian belajar mahasiswa ditinjau dari pengetahuan awal matematisnya. Penelitian ini dilakukan terhadap mahasiswa program studi pendidikan Matematika pada salah satu universitas swasta di Tangerang dengan sampel yang digunakan sebanyak 120 orang. Penelitian ini merupakan penelitian kuantitatif ex post facto dengan menggunakan desain dua faktorial. Variabel pada penelitian ini terdiri dari variabel bebas berupa keyakinan matematis, variabel moderator berupa pengetahuan awal matematis, dan variabel terikat berupa kemandirian belajar. Hasil penelitian yang didapatkan adalah: (1) mahasiswa dengan keyakinan logical consistency memiliki kemandirian belajar lebih tinggi daripada mahasiswa dengan keyakinan hafalan dan prosedural, (2) terdapat interaksi antara keyakinan matematis dan pengetahuan awal matematis (PAM) terhadap kemandirian belajar mahasiswa, (3) mahasiswa pada kelompok PAM tinggi dengan keyakinan logical consistency memiliki kemandirian belajar lebih tinggi daripada mahasiswa dengan keyakinan hafalan dan prosedural, dan (4) mahasiswa pada kelompok PAM rendah dengan keyakinan logical consistency memiliki kemandirian belajar lebih rendah daripada mahasiswa dengan keyakinan hafalan dan prosedural.